2021
DOI: 10.3390/insects12111045
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Efficacy of 30 Different Essential Oils against Varroa destructor and Honey Bee Workers (Apis mellifera)

Abstract: Essential oils and their components are generally known for their acaricidal effects and are used as an alternative to control the population of the Varroa destructor instead of synthetic acaricides. However, for many essential oils, the exact acaricidal effect against Varroa mites, as well as the effect against honey bees, is not known. In this study, 30 different essential oils were screened by using a glass-vial residual bioassay. Essential oils showing varroacidal efficacy > 70% were tested by the compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
38
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 83 publications
5
38
0
1
Order By: Relevance
“…In our experiments, the essential oil of O. heracleoticum was effective both by contact and by fumigation. The results of our study are comparable to those of Hybl et al (2021) [59] which verified the efficacy of the essential oil of Origanum vulgare against adult female Varroa mites, in laboratory conditions. Indeed, in their in vitro study, Hybl et al (2021) used the same test employed in our study (glass-vial residual bioassay) to evaluate the acaricidal activity.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In our experiments, the essential oil of O. heracleoticum was effective both by contact and by fumigation. The results of our study are comparable to those of Hybl et al (2021) [59] which verified the efficacy of the essential oil of Origanum vulgare against adult female Varroa mites, in laboratory conditions. Indeed, in their in vitro study, Hybl et al (2021) used the same test employed in our study (glass-vial residual bioassay) to evaluate the acaricidal activity.…”
Section: Discussionsupporting
confidence: 92%
“…Importantly, Hybl et al (2021) [ 59 ] estimated the mortality of Varroa mite after 2 and 4 h of essential oil exposure, with a 100% mortality rate. In the present study, following the indications of Bava et al (2021) [ 26 ], the mortality rate was evaluated one hour after EO exposure, reaching a mortality percentage of 90.9% (2 mg/mL concentration).…”
Section: Discussionmentioning
confidence: 99%
“…For these reasons, alternative methods of mite control have been promoted, such as the utilization of natural substances, particularly organic acids (such as formic acid and oxalic acid) and essential oils and their individual components (e.g. thymol) 21,22 . Although the aforementioned natural substances have displayed promising activity against Varroa , numerous studies have reported variable efficacy among treated colonies, as well as across different geographical regions and seasons 23 .…”
Section: Introductionmentioning
confidence: 99%
“…thymol). 21,22 Although the aforementioned natural substances have displayed promising activity against Varroa, numerous studies have reported variable efficacy among treated colonies, as well as across different geographical regions and seasons. 23 Consequently, there is a growing demand for new methods to control Varroa while ensuring honey bee safety.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the use of naturally origin acaricides that are safe for non-target species as human and bees is highly being promoted. Many plant essential oils exhibit considerable acaricidal activity (Sabahi et al, 2018) can be used as natural miticides and alternative to, or in rotation with synthetic miticides to give the colonies a break from chemical sublethal effects or combs contamination (Hýbl, et al, 2021). Caraway (Carum carvi L., family: Apiaceae) is a widespread plant grown everywhere in the world.…”
Section: Introductionmentioning
confidence: 99%